2012
DOI: 10.1111/j.1600-0412.2012.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes and the effect of metformin treatment in women with polycystic ovary syndrome: an overview

Abstract: This article is a review of the literature assessing pregnancy outcomes and the effect of metformin treatment among women with polycystic ovary syndrome (PCOS). A review of research published in English was undertaken using PubMed and MEDLINE databases. The weight of the available evidence suggests that pregnant women with PCOS are at an increased risk of developing gestational diabetes, hypertensive disorders of pregnancy, preterm birth and early pregnancy loss. Obesity is a contributory factor for the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 56 publications
1
34
2
Order By: Relevance
“…According to the Rotterdam criteria, PCOS diagnosis requires the presence of at least two of the three criteria (12). Women with PCOS are at an increased risk of developing GDM (13,14,15,16,17). Women with both PCOS and GDM have a higher risk of developing pregnancyinduced hypertension and preeclampsia and of delivering preterm than those with GDM only (18).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Rotterdam criteria, PCOS diagnosis requires the presence of at least two of the three criteria (12). Women with PCOS are at an increased risk of developing GDM (13,14,15,16,17). Women with both PCOS and GDM have a higher risk of developing pregnancyinduced hypertension and preeclampsia and of delivering preterm than those with GDM only (18).…”
Section: Introductionmentioning
confidence: 99%
“…However, PCOS by itself is not an independent risk factor because these patients have more assisted reproductive technologies, more chance of multiple pregnancies, and pregnancy-induced hypertension contributing to more preterm deliveries [ 17 ]. A high frequency of cervical insuffi ciency was found in PCOS, with a prevalence in the range of 3 % and incidence rate of 18 per 1,000 births, particularly in South Asian and Black women [ 14 ].…”
Section: Pcos and Adverse Pregnancy Outcomementioning
confidence: 98%
“…A metaanalysis of pregnancy outcomes in women with PCOS demonstrated a significantly higher risk of developing gestational diabetes, pregnancy-induced hypertension, pre-eclampsia and preterm birth ( Table 1) [8]. An exhaustive review of the literature assessing pregnancy outcomes and the effect of metformin treatment among women with PCOS by Ghazeeri et al [9] concluded that the weight of available evidence suggests that pregnant women with PCOS are at increased risk of developing preterm birth and hypertensive disorders of pregnancy with a prevalence of respectively 6-15% for preterm birth, 10-30% for gestational hypertension, 8-15% for pre-eclampsia. The authors concluded that metformin has proven to be effective in improving ovulation and pregnancy rates among patients receiving fertility-enhancing agents, supporting its use among anovulatory women with PCOS.…”
Section: Pregnancy Complications In Pcosmentioning
confidence: 98%